Palladium-based multi-metal composite material and preparation method and application thereof

By adding metals such as Co, Ni and Bi to the Pd-based catalyst, the amorphous structure of the polymetal composite material is formed, and the problem of insufficient activity and stability of the existing Pd-based catalyst is solved, and efficient and economical catalytic performance and long-term development are achieved. Stability, suitable for alcohol oxidation reactions and fuel cell applications.

CN119114097APending Publication Date: 2024-12-13WUYI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411071430.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-06
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The lack of catalytic activity and long-term stability of existing Pd-based catalysts in alcohol oxidation reactions leads to problems such as complex operation, high cost and poor product uniformity in commercial applications, which limits their large-scale production and application.

Method used

Using polymetal composite materials containing metals such as Pd, Pt, Co, Ni and Bi, prepared by solvothermal method to form an amorphous structure with synergistic effects, optimize the electronic structure and surface morphology of the catalyst, and improve catalytic activity and stability. .

Benefits of technology

It significantly improves catalytic activity and stability, reduces production costs, is suitable for large-scale industrial applications, conforms to the concept of green chemistry and circular economy, extends the service life of the catalyst, and shows excellent electrochemical performance in fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114097A_ABST
    Figure CN119114097A_ABST
Patent Text Reader

Abstract

The invention discloses a palladium-based multi-metal composite material and a preparation method and application thereof, the composite material comprises precious metals and non-precious metals, the precious metals comprise Pd and Pt, and the non-precious metals comprise Co, Ni and Bi. According to the preparation scheme of the novel composite material provided by the invention, the catalytic activity and the stability are greatly improved in the application of ethanol catalytic oxidation reaction. According to the scheme, the composite material is an alloy material containing precious metal and non-precious metal at the same time, and active sites of Co, Ni and Bi in the material do not exist in an isolated mode but generate a strong synergistic effect mutually. The synergistic effect promotes the effective transfer of electrons among metal elements, optimizes the charge distribution on the surface of the catalyst, and enhances the adsorption and activation capabilities of reactant molecules on the surface of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field related to metal alloy preparation, and in particular to a palladium-based multi-metal composite material and a preparation method and application thereof. Background Art

[0002] As a leader among precious metals, Pd has shown broad application prospects in many key fields such as efficient oxidation of alcohols, oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER) due to its excellent electrocatalytic performance. Its unique ability to resist CO poisoning makes it an indispensable catalyst material in the treatment of CO-containing exhaust gas and fuel cells. In certain specific catalytic scenarios, Pd can even surpass the electrocatalytic activity of traditional precious metal Pt, showing extraordinary catalytic potential.

[0003] However, the scarcity of Pd resources and its high market price have undoubtedly become bottlenecks restricting its large-scale application. In this context, in-depth exploration and optimization of the performance of Pd-based catalysts has become an important topic in the scientific research community. As the core factor that determines the catalytic performance of catalysts, the fine regulation of electronic structure has become a key path to improve catalytic efficiency. By alloying with other metals, the electronic structure of Pd can be effectively adjusted. This process not only changes the surface chemical environment of the catalyst, but also profoundly affects the adsorption and conversion behavior of the reaction intermediates, thereby achieving a significant improvement in electrocatalytic performance, surpassing the performance upper limit of single metal and some multi-metal alloy catalysts.

[0004] To overcome the above challenges of Pd-based catalysts, researchers are committed to developing diverse Pd-metal alloying strategies to form stable palladium-based compounds. Although a variety of preparation methods including mechanical alloying, melt alloying, and vapor deposition technology have been explored, these methods still face limitations such as complex operation, high cost, poor product uniformity, or difficulty in large-scale production. In particular, in reaction systems such as alcohol oxidation, the oxidation efficiency and long-term stability of multi-metal alloy catalysts are still prominent, limiting their commercialization process.

[0005] Therefore, it is particularly urgent to explore a new method for preparing multi-metallic Pd-based nanomaterials that is simple, efficient, safe and stable. This method needs to take into account both cost control and performance optimization, and aims to deeply analyze the specific influence mechanism of different metal elements and geometric configurations on the electronic structure and catalytic performance of the catalyst by precisely controlling the alloy composition, structure and even surface morphology. This not only helps to reveal the structure-activity relationship between catalyst structure and performance in theory, but also provides a scientific basis and experimental guidance for the design and synthesis of efficient, economical and environmentally friendly Pd-based catalysts. With the continuous progress in this field, it is expected to promote the widespread application of Pd-based catalysts in many fields such as energy conversion and storage, environmental protection, etc., showing great scientific significance and socio-economic value. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a palladium-based multi-metal composite material, which has strong catalytic activity.

[0007] The invention also provides a method for preparing the composite material, which is easy to operate and has good industrial application prospects.

[0008] The invention also proposes application of the composite material.

[0009] According to one aspect of the present invention, a palladium-based multi-metal composite material is provided. The composite material comprises noble metals and non-noble metals. The noble metals include Pd and Pt, and the non-noble metals include Co, Ni and Bi.

[0010] According to a preferred embodiment of the present invention, at least the following beneficial effects are achieved: the novel composite material preparation scheme proposed in the present invention shows a significant improvement in catalytic activity and stability in the application of ethanol catalytic oxidation reaction. The composite material of the scheme of the present invention is an alloy material containing both precious metals and non-precious metals. The Co, Ni, and Bi active sites inside the material do not exist in isolation, but produce a strong synergistic effect with each other. This synergistic effect promotes the effective transfer of electrons between metal elements, optimizes the charge distribution on the catalyst surface, and enhances the adsorption and activation ability of reactant molecules on the catalyst surface. The composite material of the present invention shows good selectivity and durability, can maintain high-efficiency catalytic performance for a long time, reduces the frequency of catalyst replacement and the generation of waste, and better conforms to the concept of green chemistry and circular economy. Therefore, the composite material of the present invention not only provides an efficient, economical, and environmentally friendly solution for ethanol catalytic oxidation reaction, but also provides new ideas and references for catalyst design and application in other related fields.

[0011] In some embodiments of the present invention, the non-precious metal further includes at least one of Mo and W.

[0012] In some embodiments of the present invention, the non-noble metal consists of Co, Ni and Bi.

[0013] In some embodiments of the present invention, the molar ratio of the precious metal to the non-precious metal is 1: 1 to 2. By precisely controlling the ratio and distribution of the three elements, not only the dependence on traditional high-cost precious metals is successfully reduced, thereby significantly reducing production costs, effectively alleviating the pressure caused by the scarcity of precious metal resources, but also a new path for sustainable development and green chemical processes is opened up.

[0014] In some embodiments of the present invention, the molar ratio of the noble metal to the non-noble metal is 1:1.2-1.8.

[0015] In some embodiments of the present invention, the molar ratio of Pd, Pt, Co, Ni, Bi, Mo and W is 5:1.5-2.5:2-3:4-5:1.5-2.5:2-3:3-4.

[0016] In some embodiments of the present invention, the molar ratio of Pd, Pt, Co, Ni, Bi, Mo and W is 5:2:2.2:4.2:2:2.8:3.7.

[0017] In some embodiments of the present invention, the molar ratio of Pd, Pt, Co, Ni and Bi is 5:1.5-2.5:2-3:4-5:1.5-2.5.

[0018] In some embodiments of the present invention, the molar ratio of Pd, Pt, Co, Ni and Bi is 5:2:2.2:4.2:2.

[0019] According to another aspect of the present invention, a method for preparing the above-mentioned palladium-based multi-metal composite material is provided, comprising the following steps:

[0020] A noble metal source, a non-noble metal source and a reducing solvent are mixed to obtain a reaction system, and the reaction is carried out at 100-170°C for 1-10 hours; wherein the noble metal source includes a palladium source and a platinum source, the non-noble metal source includes a cobalt source, a nickel source and a bismuth source, the reducing solvent includes a mixture of oleylamine and octadecene, and a reducing agent is added or not added to the reaction system. If added, the reducing agent includes ascorbic acid.

[0021] According to a preferred embodiment of the present invention, the preparation method has at least the following beneficial effects: a palladium-based multi-metal composite material is prepared by a simple solvent thermal method, the preparation process is simple, the obtained sample structure is stable, and even if the input amount of each raw material is increased in the same proportion, the sample structure and morphology remain unchanged, which is suitable for large-scale industrial applications. During the preparation process, the precious metal and the non-precious metal are reduced, and an amorphous structure is formed between the non-precious metals, and there is a better synergistic effect between the active sites, so that the composite material has a higher catalytic activity. In some embodiments of the present invention, the volume ratio of oleylamine to octadecene is 1 to 2:1.

[0022] In some embodiments of the present invention, the volume ratio of oleylamine to octadecene is 1.5:1.

[0023] In some embodiments of the present invention, the ratio of the sum of the amounts of the noble metal source and the non-noble metal source to the molar amount of the reducing agent is 1 to 1.1:1.

[0024] In some embodiments of the present invention, the ratio of the sum of the amounts of the noble metal source and the non-noble metal source to the molar amount of the reducing agent is 1.04-1.05:1.

[0025] In some embodiments of the present invention, the noble metal source is added to the reducing solvent at a standard of 0.006 to 0.008 mol / L.

[0026] In some embodiments of the present invention, the noble metal source is added to the reducing solvent at a standard of 0.007 mol / L.

[0027] In some embodiments of the present invention, the noble metal source and the non-noble metal source are both added in the form of a salt, and the salt is at least one of acetylacetonate, chloride, and acetate. Other salts may also be added.

[0028] In some embodiments of the present invention, W and Mo in the non-precious metal source are added in the form of carbonyl compounds.

[0029] In some embodiments of the present invention, the preparation method further comprises a post-treatment step: after the reaction product is separated into solid and liquid, it is washed with ethanol and cyclohexane for 4 to 6 times and dried.

[0030] Another aspect of the present invention provides the use of the composite material in ethanol and / or methanol oxidation catalysts.

[0031] According to another aspect of the present invention, an electrode for a fuel cell is provided, comprising the above composite material.

[0032] According to another aspect of the present invention, a fuel cell is provided, comprising the above-mentioned electrode.

[0033] The composite material of the present invention has high catalytic activity for ethanol and / or methanol oxidation, and has excellent stability and durability, and can maintain high performance for a long time in the complex working environment of the fuel cell, and effectively resist electrochemical corrosion and poisoning. This advantage makes it a strong candidate to replace traditional precious metal catalysts, and it can be used as an electrode of fuel cells, effectively reducing the production cost of fuel cells, and has good application prospects in the field of new energy.

[0034] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0036] Figure 1is a SEM image of the composite material prepared in Example 1 of the present invention.

[0037] Figure 2 This is a SEM image of the composite material prepared in Example 1 of the present invention at another magnification.

[0038] Figure 3 is a SEM image of the composite material prepared in Example 2 of the present invention.

[0039] Figure 4 3 is a SEM image of the composite material prepared in Example 3 of the present invention.

[0040] Figure 5 It is a SEM picture of the composite material prepared in Comparative Example 1 of the present invention.

[0041] Figure 6 is the XRD diagram of the composite material prepared in Example 1 of the present invention.

[0042] Figure 7 This is the XRD diagram of the composite material prepared in Example 2 of the present invention.

[0043] Figure 8 3 is the XRD diagram of the composite material prepared in Example 3 of the present invention.

[0044] Fig. 9 It is the XRD diagram of the composite material prepared in Comparative Example 1 of the present invention.

[0045] Fig.10 It is the XRD diagram of the composite material prepared in Comparative Example 2 of the present invention.

[0046] Fig.11 It is a comparison chart of XRD of the composite materials prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 2.

[0047] Fig.12 This is an EDS characterization result diagram of the composite material prepared in Example 1 of the present invention.

[0048] Fig.13 This is an EDS characterization result diagram of the composite material prepared in Example 2 of the present invention.

[0049] Fig.14 This is an EDS characterization result diagram of the composite material prepared in Comparative Example 1 of the present invention.

[0050] Fig.15 This is an EDS characterization result diagram of the composite material prepared in Comparative Example 2 of the present invention.

[0051] Fig.16 This is a test graph of the catalytic activity of the composite material prepared in Example 1 of the present invention for ethanol oxidation.

[0052] Fig.17This is a test chart of the catalytic activity of the composite material prepared in Example 1 of the present invention for methanol oxidation.

[0053] Fig.18 This is a test chart of the catalytic activity of the composite material prepared in Examples 1 and 2 of the present invention for ethanol oxidation.

[0054] Fig.19 This is a test chart of the catalytic activity of the composite materials prepared in Examples 1 and 3 of the present invention for methanol oxidation.

[0055] Fig. 20 This is a test chart of the catalytic activity of the composite materials prepared in Example 1 and Comparative Example 1 of the present invention for methanol oxidation.

[0056] Fig.21 This is a test chart of the catalytic activity of the composite materials prepared in Example 1 and Comparative Example 2 of the present invention for methanol oxidation. DETAILED DESCRIPTION

[0057] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be reagents and materials obtained from commercial channels. Unless otherwise specified, the same parameter in each embodiment has the same value. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limitations on the present invention.

[0058] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0059] Example 1

[0060] In this example, a palladium-based multi-metal composite material is prepared, which is composed of a noble metal matrix and a non-noble metal supported on the matrix, wherein the noble metal is composed of Pd and Pt, and the non-noble metal is composed of Co, Ni and Bi. The specific process is as follows:

[0061] 3mL oleylamine and 2mL octadecene are used as solvent and reducing agent, and then 0.005 mol / L acetylacetonate palladium, 0.002 mol / L acetylacetonate platinum, 0.0022 mol / L acetylacetonate cobalt, 0.0042 mol / L nickel chloride hexahydrate, 0.0148 mol / L ascorbic acid and 0.002 mol / L bismuth acetate are added to a round-bottom flask, ultrasonically dissolved, and then placed in an oil bath, heated to 170°C, and reacted at this temperature for 6 hours. After the reaction is completed, centrifuge at 15,000 rpm for 5 minutes, first use a mixture of ethanol and cyclohexane (the volume ratio of the two is 9:1), then wash with ethanol 3 to 5 times, and dry at 60°C.

[0062] Example 2

[0063] In this example, a palladium-based multi-metal composite material was prepared. The specific process was as follows:

[0064] 3mL oleylamine and 2mL octadecene are used as solvent and reducing agent, and then 0.005 mol / L acetylacetonate palladium, 0.002 mol / L acetylacetonate platinum, 0.0022 mol / L acetylacetonate cobalt, 0.0042 mol / L nickel chloride hexahydrate, 0.0028 mol / L hexacarbonyl tungsten and 0.002 mol / L bismuth acetate are added to a round-bottom flask, ultrasonically dissolved, and then placed in an oil bath, the oil bath temperature is heated to 170℃, and reacted at different temperatures for 6h. After the reaction is completed, centrifuge at 15000 rpm for 5 minutes, first use a mixture of ethanol and cyclohexane (the volume ratio of the two is 9:1), then wash with ethanol 3 to 5 times, and dry at 60℃.

[0065] Example 3

[0066] In this example, a palladium-based multi-metal composite material was prepared. The specific process was as follows:

[0067] 3mL oleylamine and 2mL octadecene were used as solvent and reducing agent, and then 0.005mol / L acetylacetonate palladium, 0.002mol / L acetylacetonate platinum, 0.0022mol / L acetylacetonate cobalt, 0.0042mol / L nickel chloride hexahydrate, 0.0037mol / L hexacarbonyl molybdenum and 0.002mol / L bismuth acetate were added to a round-bottom flask, and dissolved by ultrasound, and then placed in an oil bath, the oil bath temperature was heated to 170℃, and reacted at different temperatures for 6h. After the reaction was completed, centrifuged at 15000 rpm for 5 minutes, first washed with a mixture of ethanol and cyclohexane (the volume ratio of the two was 9:1), then washed with ethanol 3 to 5 times, and dried at 60℃.

[0068] Comparative Example 1

[0069] In this example, a palladium-based multi-metal composite material was prepared. The specific process was as follows:

[0070] 3mL oleylamine and 2mL octadecene are used as solvent and reducing agent, and then 0.005mol / L acetylacetonate palladium, 0.002mol / L acetylacetonate platinum, 0.0022mol / L acetylacetonate cobalt, 0.0042mol / L nickel chloride hexahydrate, 0.0027mol / L glucose, 0.014mol / L sodium citrate and 0.002mol / L bismuth acetate are added to a round-bottom flask, ultrasonically dissolved, and then placed in an oil bath, the oil bath temperature is heated to 170℃, and reacted at different temperatures for 6h. After the reaction is completed, 15000 rpm, first with ethanol and cyclohexane mixture (the volume ratio of the two is 9:1), then washed with ethanol 3 to 5 times, and dried at 60℃.

[0071] Comparative Example 2

[0072] In this example, a palladium-based multi-metal composite material was prepared. The specific process was as follows:

[0073] 3 mL of oleylamine and 2 mL of octadecene were used as a solvent and a reducing agent, and 0.005 mol / L of acetylacetonate palladium, 0.002 mol / L of acetylacetonate platinum, 0.0022 mol / L of acetylacetonate cobalt, 0.0042 mol / L of nickel chloride hexahydrate, 0.0667 mol / L of urea, 0.0148 mol / L of ascorbic acid and 0.002 mol / L of bismuth acetate were added into a round-bottom flask.

[0074] Dissolve it by ultrasound, then put it in an oil bath, heat it to 170℃, and react it at this temperature for 6 hours. After the reaction, centrifuge it at 15000 rpm for 5 minutes, first wash it with a mixture of ethanol and cyclohexane (the volume ratio of the two is 9:1), then wash it with ethanol for 3 to 5 times, and dry it at 60℃.

[0075] Test Case

[0076] This test example tests the morphology, composition and performance of the composite materials prepared in the examples and comparative examples.

[0077] 1. Morphology characterization

[0078] The composite materials prepared in the examples and comparative examples were tested for their morphology by scanning electron microscopy (SEM). The SEM morphology of the composite material (CoPtPdBiNi) sample obtained by reacting at 170°C for 6h in Example 1 is shown in the following figure: Figures 1-2 The scanning electron microscope image of the product obtained in Example 2 is shown in Figure 3 As shown, the scanning electron microscope image of the product obtained in Example 3 is as follows Figure 4 As shown, the scanning electron microscope image of the product obtained in Comparative Example 1 is as follows Figure 5 As shown. Figures 1-2 It can be seen from the figure that the composite material prepared by the embodiment of the present invention is in sheet form. Figure 3It can be seen that although the microstructure of the composite material with tungsten hexacarbonyl added is still flaky, its dispersion is lower than that of the composite material without tungsten hexacarbonyl added. Figure 4 It can be seen that the dispersibility of the composite material generated by adding molybdenum hexacarbonyl is still lower than that of the composite material in Example 1 without adding molybdenum hexacarbonyl. Figure 5 It can be seen that a layer of organic matter is attached to the surface of the composite material prepared in Comparative Example 1 of the present invention.

[0079] 2. Composition determination

[0080] The X-ray diffraction (XRD) of the composite material prepared in Example 1 is as follows: Figure 6 As shown in the figure, it can be seen that the diffraction peaks of palladium and platinum are mainly present, and the diffraction peaks of other metals are not obvious. Therefore, on the one hand, due to its relatively low content, on the other hand, it also indicates that it may exist in an amorphous form.

[0081] The XRD pattern of the composite material obtained in Example 2 is as follows: Figure 7 As shown, the diffraction peaks of palladium and platinum are also mainly present, and the diffraction peaks of other metals are not obvious.

[0082] The XRD characteristics of the composite material obtained in Example 3 are as follows: Figure 8 As shown, the diffraction peaks of palladium and platinum are also mainly present, and the diffraction peaks of other metals are not obvious.

[0083] The XRD pattern of the composite material obtained in Comparative Example 1 is as follows: Fig. 9 As shown in the figure, it can be seen that the position of the diffraction peak is not obvious, even the diffraction peaks of palladium and platinum are basically not obvious.

[0084] The XRD characteristics of the composite material obtained in Comparative Example 2 are as follows: Fig.10 As shown. Except for palladium and platinum, the diffraction peaks of other metals are not obvious.

[0085] The XRD results of the above materials are summarized as follows: Fig.11 As shown. Fig.11 It can be seen that there are obvious palladium and platinum diffraction peaks in Examples 1 to 3 and Comparative Examples 1 to 2, while other metal diffraction peaks are not obvious.

[0086] The EDS characterization results of the composite material prepared in Example 1 are as follows: Fig.12 As shown in the figure, it can be seen that the composite material contains Pd, Pt, Ni, Co and Bi.

[0087] The EDS characterization results of the composite material prepared in Example 2 are as follows: Fig.13 As shown in the figure, it can be seen that the composite material contains W in addition to Pd, Pt, Ni, Co and Bi. Fig.12 and13 It can be seen that after adding the reducing agent ascorbic acid, the reduced amounts of Pd, Pt, Ni, Co and Bi are significantly higher than when no reducing agent is added.

[0088] The EDS analysis results of Example 3 are Fig.13 Similarly, the presence of Mo in the composite material can be confirmed by EDS.

[0089] The EDS characterization results of the composite material prepared in Comparative Example 1 are as follows: Fig.14 As shown in the figure, it can be seen that the composite material contains Pd, Pt, Ni and Co, among which the atomic proportions of Ni and Co are higher than those of Pd and Pt.

[0090] The EDS characterization results of the composite material obtained in Comparative Example 2 are as follows: Fig.15 As shown in the figure, it can be seen that the composite material contains Pd, Pt, Ni, Co and Bi, among which the atomic ratios of Ni, Co and Bi are significantly reduced compared with those in Example 1.

[0091] 3. Performance Characterization

[0092] The catalytic activity of the composite materials prepared in the above embodiments and comparative examples as ethanol or methanol oxidation catalysts was tested, and commercial Pt / C purchased from the market was also used for simultaneous testing as a comparison. Test conditions: A three-electrode test method was used, with a glassy carbon electrode coated with a composite material agent as the working electrode, a saturated calomel as the reference electrode, a Pt sheet as the counter electrode, and an electrolyte of 1.0M KOH and 1.0M methanol (or ethanol) aqueous solution to carry out the test. The CV test interval was -0.97V to 0.3V, and the scan rate was 50mV / s.

[0093] Mass activity in the test results = measured current density / EDS measured precious metal mass

[0094] The catalytic performance of the composite material in Example 1 for ethanol and methanol oxidation reactions is as follows: Fig.16 and 17 shown.

[0095] from Fig.16 It can be seen that during the catalytic oxidation of ethanol, the peak voltage is at -0.008V (relative to the calomel electrode), the peak current density is about 9168.6mA / g, and after 1000 CV cycles, the current density is 2662.3mA / g. The peak voltage of commercial Pd / C is -0.153V, and the current density is 543.7mA / g. After 1000 CV cycles, the current density of CoPtPdNiBi AA is 2662.3mA / g, which still has significantly higher catalytic activity than commercial Pd / C and shows good catalytic stability.

[0096] from Fig.17 It can be seen that during the catalytic methanol oxidation process, the peak voltage is at -0.062V (relative to the calomel electrode), the peak current density is about 2816.3mA / g, and after 1000 CV cycles, the current density is 476.2mA / g. The peak voltage of commercial Pd / C is -0.146V, and the current density is 252.25mA / g. The above data comparison shows that the composite material of the embodiment of the present invention has a higher catalytic activity.

[0097] Compared with the commercial Pd / C electrocatalyst widely used in the market, the composite material prepared by the embodiment of the present invention shows significant advantages when used as a catalyst. Specifically, the catalyst has a low starting potential, which means that the catalytic reaction can be started at a lower voltage, effectively reducing energy loss; at the same time, its peak current density is significantly improved, showing excellent current carrying capacity and faster electron transfer rate, which is crucial for improving the output power of fuel cells. In addition, the catalyst also shows excellent catalytic stability, that is, it can still maintain efficient catalytic performance under long-term operation or extreme conditions, which is of great significance for extending the service life of fuel cells.

[0098] It is speculated that these superior properties may be derived from the unique microstructure and composition design of the catalyst. Specifically, the present invention cleverly embeds a variety of metal sources into the composite material and forms a partial amorphous structure. The introduction of this amorphous structure, on the one hand, adjusts the electronic structure of the material to move the d-band center downward, thereby weakening the interaction strength between the catalyst surface and the reaction adsorbate, reducing the energy barrier in the catalytic process, and thus improving the catalytic activity; on the other hand, the amorphous structure usually has more defects and active sites, which can more effectively promote the adsorption and conversion of reactants, further enhancing the catalytic effect. In addition, the presence of an amorphous structure may also enhance the corrosion resistance and stability of the catalyst, enabling it to maintain long-term catalytic performance in harsh working environments.

[0099] In summary, the catalyst prepared in the embodiment of the present invention, with its low starting potential, high peak current density and excellent catalytic stability, is expected to become an ideal electrocatalyst for the next generation of high-performance fuel cells, and promote the further development and application of fuel cell technology.

[0100] The test results of the catalytic effect of Examples 1-2 and commercial Pd / C on ethanol oxidation are as follows: Fig.18As shown. It can be seen from the figure that when W is introduced into the composite material in addition to Co, Ni and Bi, its catalytic activity is weaker than that of the composite material containing only Co, Ni and Bi, but it is still significantly higher than that of commercial Pd / C. It is speculated that the reason may be that no reducing agent was added, which makes the reduction effect of Co, Ni and Bi on the surface of the composite material quite different from that in Example 1. At the same time, the introduction of W changes the surface properties and active sites of the composite material containing only Co, Ni and Bi, or may change the reaction path of the ethanol oxidation process. The dispersibility decreases, resulting in a decrease in the specific surface area and a decrease in the number of activation sites, which leads to a decrease in catalytic activity.

[0101] The test results of the catalytic effects of Examples 1 and 3 and Comparative Example 1 and commercial Pd / C on ethanol oxidation are as follows: Fig.19 As shown. It can be seen from the figure that when Mo is introduced into the composite material in addition to Co, Ni and Bi, its catalytic activity is weaker than that of the composite material containing only Co, Ni and Bi, but it is still significantly higher than that of commercial Pd / C. It is speculated that the reason may be that no reducing agent is added, which makes the reduction effect of Co, Ni and Bi on the surface of the composite material quite different from that in Example 1. At the same time, the introduction of Mo changes the surface properties and active sites of the composite material containing only Co, Ni and Bi, or may change the reaction path of the ethanol oxidation process. The dispersibility decreases, resulting in a decrease in the specific surface area and a decrease in the number of activation sites, which leads to a decrease in catalytic activity.

[0102] The test results of the catalytic effect of Example 1 and Comparative Example 1 and commercial Pd / C on ethanol oxidation are as follows: Fig. 20 As shown in the figure, when glucose and sodium citrate, which also have reducing properties, are used instead of ascorbic acid, the prepared composite material has almost no catalytic activity. This may be because glucose and the like easily form a film on the surface of the composite material, making the catalytic reaction difficult to proceed.

[0103] The test results of the catalytic effect of Example 1 and Comparative Example 2 on ethanol oxidation with commercial Pd / C are as follows: Fig.21 As shown in the figure, it can be seen that after the addition of urea, the presence of N may cause the generated reactants to form a film-like substance, which affects the catalytic activity.

[0104] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A palladium-based multi-metal composite material, characterized in that: The composite material comprises noble metals and non-noble metals, wherein the noble metals include Pd and Pt, and the non-noble metals include Co, Ni and Bi; preferably, the non-noble metals further include at least one of W and Mo; more preferably, the non-noble metals consist of Co, Ni and Bi.

2. The palladium-based multi-metal composite material according to claim 1, characterized in that: The molar ratio of the noble metal to the non-noble metal is 1:1-2; preferably, the molar ratio of the noble metal to the non-noble metal is 1:1.2-1.

8.

3. The palladium-based multi-metal composite material according to claim 1, characterized in that: The molar ratio of Pd, Pt, Co, Ni and Bi is 5:1.5-2.5:2-3:4-5:1.5-2.5; preferably, the molar ratio of Pd, Pt, Co, Ni and Bi is 5:2:2.2:4.2:

2.

4. The method for preparing the palladium-based multi-metal composite material according to any one of claims 1 to 3, characterized in that: The steps include: A noble metal source, a non-noble metal source and a reducing solvent are mixed to obtain a reaction system, and the reaction is carried out at 100-170° C. for 1-10 hours; wherein the noble metal source includes a palladium source and a platinum source, the non-noble metal source includes a cobalt source, a nickel source and a bismuth source, the reducing solvent includes a mixture of oleylamine and octadecene, and a reducing agent is added or not added to the reaction system. If added, the reducing agent is ascorbic acid.

5. The preparation method according to claim 4, characterized in that: The volume ratio of oleylamine to octadecene is 1-2:1; preferably, the volume ratio of oleylamine to octadecene is 1.5:

1.

6. The preparation method according to claim 4, characterized in that: The ratio of the sum of the amounts of the precious metal source and the non-precious metal source to the molar amount of the reducing agent is 1 to 1.1:1; preferably, the ratio of the sum of the amounts of the precious metal source and the non-precious metal source to the molar amount of the reducing agent is 1.04 to 1.05:

1.

7. The preparation method according to claim 4, characterized in that: The noble metal source is added to the reducing solvent at a standard of 0.006-0.008 mol / L; preferably, the noble metal source is added to the reducing solvent at a standard of 0.007 mol / L.

8. Use of the composite material according to any one of claims 1 to 3 in an ethanol and / or methanol oxidation catalyst.

9. An electrode for a fuel cell, characterized in that: The method comprises the composite material according to any one of claims 1 to 3.

10. A fuel cell, characterized in that: Comprising the electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Preparation method of platinum-rhodium alloy, preparation method of platinum-rhodium alloy catalyst and application of platinum-rhodium alloy catalyst

    CN114618482A

  • Palladium-based hydride and preparation method and application thereof

    CN118007163A

  • Preparation of PtSnBiPdIn high-entropy alloy nano material with hollow structure and application of PtSnBiPdIn high-entropy alloy nano material in electrocatalytic oxidation

    CN118404080A

  • Alloy metallic nanostructure and method of it for fuel cell

    KR1020110026648A